2020
DOI: 10.3892/etm.2020.8606
|View full text |Cite
|
Sign up to set email alerts
|

Infection with hepatitis C virus in hemodialysis patients: An overview of the diagnosis and prevention rules within a hemodialysis center (Review)

Abstract: Increase in the number of patients with chronic kidney disease (CKD) calls for improved management of these patients. In stage 5 CKD, when the initiation of renal replacement therapy (RRT) becomes necessary, there is an increase in the infection risk of the patients and immunological tests for hepatitis C virus (HCV) detection turn positive at an alarmingly higher rate compared to general population. With the introduction into clinical practice of diagnostic tests, the increased prevalence of HCV among CKD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…We speculate that this result might reflect the fact that the appearance of anti-HCV is not evidence of present infection; it is regularly used in preliminary screening of HCV infection as an indicator of previous HCV infection. After the moment of the HCV infection, the serological tests allow for anti-HCV antibodies detection on 7-8 weeks [33]. Anti-HCV antibodies may persist indefinitely in chronic infection patients.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this result might reflect the fact that the appearance of anti-HCV is not evidence of present infection; it is regularly used in preliminary screening of HCV infection as an indicator of previous HCV infection. After the moment of the HCV infection, the serological tests allow for anti-HCV antibodies detection on 7-8 weeks [33]. Anti-HCV antibodies may persist indefinitely in chronic infection patients.…”
Section: Discussionmentioning
confidence: 99%
“…After its identification in 1989, it has been observed that patients on renal replacement therapy have commonly detectable anti-HCV antibody in serum. The frequency of patients with positive serology for anti-HCV antibody who undergo maintenance dialysis is still higher than that observed in the respective general population of developed [2] or emerging countries [2,[5][6][7][8][9][10][11][12][13][14][15]. Infection with chronic HCV infection leads to chronic liver disease with its attendant complications (cirrhosis, hepatocellular carcinoma, and hepatocellular failure).…”
Section: Current Epidemiology Of Hcv In Chronic Kidney Diseasementioning
confidence: 99%
“…HCV induces a low-amplitude T and B lymphocyte-mediated immune response, which leads to long-lasting infection and production of non-specific biochemical markers (3)(4)(5). Thus, disease progression is difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…Among the extrahepatic manifestations of HCV infection, an important role is played by renal involvement, being described as a series of histopathological forms: Proliferative membrane glomerulonephritis, IgA nephropathy, focal segmental glomerulosclerosis, fibrillar glomerulonephritis, tubulointerstitial nephropathy and thrombosis ( 2 , 3 ). The prevalence of HCV infection in patients with chronic kidney disease (CKD) is between 5 and 60% in developed countries, with a certain predominance in hemodialysis patients ( 3 ). HCV-positive hemodialysis patients show a decreased survival rate; the risk of death associated with liver disease being aggravated by the increased risk of cardiovascular death attributed to malnutrition and chronic inflammation ( 4 ).…”
Section: Introductionmentioning
confidence: 99%